PENGARUH MINUMAN SUPLEMEN, MINUMAN ELEKTROLIT DAN AIR NORMAL TERHADAP KINERJA OLAHRAGA - muhammad muhyi (Program Studi Pendidikan Jasmani, Fakultas Pedagogik dan Psikologi (FPeP), 2015)
This research is a field experimental research. The subject population used for this research is 159 male of the entire FIK UNESA of Surabaya State University, from students which a sample of 60 is randomly selected. After that split in to three groups and per groups are 20. The research design used is the â€œ Randomized Control Group Pretest Posttest Designâ€. After field research, the data collected and analyzed by â€œAnalysis of Varianceâ€ (ANOVA). First, analyzing influence drinks on speed, the result is F probabilities is more than alpha (0.0605>0,05). It means that all drinks have the same effect on speed. Second, analyzing influence supplement on exercise heart rate, the result is alpha with significance levels 0.05, with probabilities is under than alpha 0.049. It means not all drinks have the same effect heart rate. Which drinks have different influence is use Test-low significance different (LSD). The result showed that aqua water give different effect â€“ 12.900. Finally aqua water give the different effect to ergogenic aids. Conclusion drawn from this research are: 1. Supplement drinks, electrolyte drinks and normal water have the same effect on ergogenic aids related to speed, 2. Having different effect supplement drinks, electrolyte drinks and normal water on ergogenics aids related to heart rate, 3. Normal water have great effect on ergogenic aids related to heart rate, 4. Normal water better because pulse rate is lower down that cardiac workload effect is slow,. Normal water is better than supplement drinks and electrolyte drinks for middle distance.